More than the Lesion: Unraveling the Complexities of Endometriosis-Associated Pain - Alzamora-Schmatz, Maria C.; Gubbels, Ashley (Seminars in Reproductive Medicine, 2025)
Endometriosis is a chronic, estrogen-dependent inflammatory disorder characterized by ectopic endometrium-like tissue, leading to debilitating pain and reduced quality of life. Pain is the hallmark of endometriosis, with individuals experiencing dysmenorrhea, dysuria, dyschezia, dyspareunia, and chronic pelvic pain. However, pain does not always correlate with the severity or location of the lesions, which suggests additional factors are involved in the generation of endometriosis-associated pain. The underlying mechanisms are multifactorial, involving peripheral and central sensitization, inflammation, aberrant innervation, immune dysregulation, and hormonally influenced processes. Additionally, many individuals with endometriosis experience comorbid pain syndromes, including pelvic floor dysfunction (PFD), irritable bowel syndrome, interstitial cystitis, abdomino-pelvic myalgia, and vulvar vestibulodynia. These conditions share overlapping pathophysiological mechanisms, such as cross-sensitization of pelvic organs and maladaptive neuroplastic changes, further amplifying pain perception. Despite advances in understanding these mechanisms, current treatment strategies remain inadequate, with hormonal suppression and surgical intervention providing variable relief. A comprehensive, multimodal approach targeting neuroinflammatory pathways, PFD, and central sensitization may be essential for improving pain management. Further research is needed to refine therapeutic strategies and develop targeted interventions for this challenging condition.
Keywords: endometriosis; pelvic pain; cross sensitization; comorbid pain syndromes; endometriosis-associated pain